The precision and torque production of common hip adductor squeeze tests used in elite football - Light, N.; Thorborg, K. (Journal of Science and Medicine in Sport, 2016)
Objectives: Decreased hip adductor strength is a known risk factor for groin injury in footballers, with clinicians testing adductor strength in various positions and using different protocols. Understanding how reliable and how much torque different adductor squeeze tests produce will facilitate choosing the most appropriate method for future testing. In this study, the reliability and torque production of three common adductor squeeze tests were investigated. Design: Test-retest reliability and cross-sectional comparison. Methods: Twenty elite level footballers (16-33 years) without previous or current groin pain were recruited. Relative and absolute test-retest reliability, and torque production of three adductor squeeze tests (long-lever in abduction, short-lever in adduction and short-lever in abduction/external rotation) were investigated. Each participant performed a series of isometric strength tests measured by hand-held dynamometry in each position, on two test days separated by two weeks. Results: No systematic variation was seen for any of the tests when using the mean of three measures (ICC = 0.84-0.97, MDC% = 6.6-19.5). The smallest variation was observed when taking the mean of three repetitions in the long-lever position (ICC = 0.97, MDC% = 6.6). The long-lever test also yielded the highest mean torque values, which were 69% and 11% higher than the short-lever in adduction test and short-lever in abduction/external rotation test respectively (p < 0.001). Conclusions: All three tests described in this study are reliable methods of measuring adductor squeeze strength. However, the test performed in the long-lever position seems the most promising as it displays high test-retest precision and the highest adductor torque production.